2020
DOI: 10.1002/app.48906
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel early‐strength polycarboxylate superplasticizer and its performances in cementitious system

Abstract: A novel early-strength type polycarboxylate superplasticizer (PCE) was synthesized by a new design of molecule structure such as introducing long polyoxyethlene side chains, functional monomer (2-acrylamide-2-methylpropanesulfonic acid), and optimizing monomer composition. In this study, with introducing the sulfonate groups into PCE structure, its dispersion capacity and the absorbed amount are increased firstly and then decreased, but the retardation hydration effect is weakened gradually. The molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…When the polymer content was continually increased, the dispersion effect of SP‐E was better than that of SP‐N, while the increasing trend for the fluidity of cement pastes containing SP‐N tended to decelerate with an increase of the superplasticizer dosages. The data in Figure 4 showed that the fluidity of cement slurries with the two superplasticizers increased to a maximum value at 60 min, which might have been due to the gradual increase in the adsorption capacity of superplasticizers on the surface of cement particles,as reported in the literature that the dispersion property of superplasticizers was based on the adsorption process 5,8,19 . Moreover, the ester or amide groups in the two crosslinking agents underwent hydrolysis and released anchoring groups to stimulate better adsorption of the polymers onto the cement particles, thus enhancing the dispersion between cement particles and in turn increasing the fluidity of cement slurries 14 .…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…When the polymer content was continually increased, the dispersion effect of SP‐E was better than that of SP‐N, while the increasing trend for the fluidity of cement pastes containing SP‐N tended to decelerate with an increase of the superplasticizer dosages. The data in Figure 4 showed that the fluidity of cement slurries with the two superplasticizers increased to a maximum value at 60 min, which might have been due to the gradual increase in the adsorption capacity of superplasticizers on the surface of cement particles,as reported in the literature that the dispersion property of superplasticizers was based on the adsorption process 5,8,19 . Moreover, the ester or amide groups in the two crosslinking agents underwent hydrolysis and released anchoring groups to stimulate better adsorption of the polymers onto the cement particles, thus enhancing the dispersion between cement particles and in turn increasing the fluidity of cement slurries 14 .…”
Section: Resultsmentioning
confidence: 64%
“…The data in Figure 4 showed that the fluidity of cement slurries with the two superplasticizers increased to a maximum value at 60 min, which might have been due to the gradual increase in the adsorption capacity of superplasticizers on the surface of cement particles,as reported in the literature that the dispersion property of superplasticizers was based on the adsorption process. 5,8,19 Moreover, the ester or amide groups in the two crosslinking agents underwent hydrolysis and released anchoring groups to stimulate better adsorption of the polymers onto the cement particles, thus enhancing the dispersion between cement particles and in turn increasing the fluidity of cement slurries. 14 In addition, the adsorption capacity of SP-E on the surface of cement particles is higher than that of SP-N, and it is evident that SP-E provides a stronger dispersion effect than SP-N.…”
Section: Effect Of Polymers On the Fluidity Of Cement Pastesmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, larger molecular weight polyoxyethylene ether macromonomers (M w greater than 3000 Da) are mainly used for the synthesis of early-strength PCE. 25,26 Compared with ordinary PCEs, these early-strength PCEs have long side chains, and short main chains. The hydrophilic side chains can allow more water to surround cement particles, thus ensuring the normal hydration of cement and improving the early strength of concrete.…”
Section: Introductionmentioning
confidence: 99%